Optimalisasi Peran Koperasi Nelayan Melalui Kolaborasi dengan Fintech (Studi Di Koperasi Mina Bahari ‘45 Pantai Depok Bantul) - Erna Tri Rusmala Ratnawati; Fifink Praiseda Alviolita; Gusti Fadhil Fithrian Luthfan (Jurnal Restorative Justice, 2021)
Coastal communities in fishing villages throughout Indonesia have the potential to be empowered to optimize the people's economic strength. This is in line with Indonesia's ideals as the world's maritime axis. However, the problems faced by Mina Bahari Cooperative ‘45 Depok Beach, Bantul, Special Region of Yogyakarta as one of the legal entity fishermen cooperatives in Indonesia, are institutional problem and short of capital in terms of financing as well as competition with moneylenders. This research is using empirical juridical methods, with sociological juridical approaches and technical analysis of descriptive qualitative data. The aim of this research is to optimize the role of fishing cooperatives as legal entities in facing the challenges of the industrial revolution 4.0 in the future to reach coastal communities that are classified as unbankable. Key-words: coastal communities, cooperative, industrial revolution 4.0